(untitled) (Relevant Tomorrow / Aktualu rytoj, 2022)
Russia’s war against Ukraine has made the research on the historical logic and socio-ideological semantics of Putin regime’s propaganda “arguments” that supposedly justify aggression against a sovereign state relevant. The article compares the notions of folk traditions and customs exploited by 19th-century Russian intellectuals, i.e., Slavophiles and right-wing Narodniks, and in Putin regime’s propaganda in the 2000s-2020s, which function as a set of mythologems and ideologemes. It raises the question of the historical and political appropriation of Slavophile and right-wing Narodnik ideology in Putin regime’s propaganda used in the various contexts of the war in Ukraine. The research highlights an ambiguity: on the one hand, it is erroneous to directly link the postulates of the Russian political regime of the early 21st century to the conservative political thought of 19th-century Russia (Slavophiles) and the Narodnik ideology. On the other hand, the fundamentals of the notions of folk traditions and customs formulated by the Slavophiles and the right-wing Narodniks of the 19th century are still alive in today’s Russian cultural memory, and they are used as elements of political populism in Putin’s propaganda. The article argues that the partial appropriation of the ideas of the 19th-century Russian Slavophiles and the right-wing Narodniks should be treated as one of the elements of situational ‘traditionalism’ used by political populism and not as a historical continuity in the literal sense of the word.